Border Ecology Art and Environmental Crisis at the Margins - Sheren, Ila Nicole (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Border Ecology is an important and accessible art historical analysis of mainly digital art and its borderlands references that promises to ignite new conversations in Border Studies, American Studies, Environmental Studies, just to name a few fields. Border Ecology considers both well-known and lesser known artworks, and brilliantly challenges the reader to reconsider what is seen and visible and what is not." -John-Michael H. Warner, Kent State University, USA This book analyzes how contemporary visual art can visualize environmental crisis. It draws on Karen Barad's method of "agential realism," which understands disparate factors as working together and "entangled." Through an analysis of digital eco art, the book shows how the entwining of new materialist and decolonized approaches accounts for the nonhuman factors shaping ecological crises while understanding that a purely object-driven approach misses the histories of human inequality and subjugation encoded in the environment. The resulting synthesis is what the author terms a border ecology, an approach to eco art from its margins, gaps, and liminal zones, deliberately evoking the idea of an ecotone. This book is suitable for scholarly audiences within art history, criticism and practice, but also across disciplines such as the environmental humanities, media studies, border studies and literary eco-criticism. Ila Nicole Sheren is Associate Professor in the Department of Art History & Archaeology at Washington University in St. Louis, USA. Her first book Portable Borders: Performance Art and Politics on the U.S. Frontera since 1984 (2015), focused on the shifting definition of site-specificity in art of the U.S.-Mexico border region.
Chapter one: Introduction -- Chapter two: The Boundaries of the Map -- Chapter three: Landscapes of Slow Violence -- Chapter four: Entanglements -- Chapter five: Border Crossers -- Chapter six: Conclusions and New Directions: Border Art for a Border Ecology.
Keywords: Art, Modern -- 21st century; Communication in the environmental sciences; Digital media; Arts; Contemporary Art; Environmental Communication; Digital and New Media; Arts